2016
DOI: 10.1002/2016gl068461
|View full text |Cite
|
Sign up to set email alerts
|

First measurement of horizontal wind and temperature in the lower thermosphere (105–140 km) with a Na Lidar at Andes Lidar Observatory

Abstract: We report the first measurement of nighttime atmospheric temperature and horizontal wind profiles in the lower thermosphere up to 140 km with the Na lidar at Andes Lidar Observatory in Cerro Pachón, Chile (30.25°S, 70.74°W), when enhanced thermospheric Na was observed. Temperature and horizontal wind were derived up to 140 km using various resolutions, with the lowest resolution of about 2.7 hr and 15 km above 130 km. Thus, the measurements span 60 km in vertical, more than double the traditional 25 km. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
3
60
0
Order By: Relevance
“…Although we are unable to compare with those in the polar region or tropic, as no statistics is available, it is much lower than the 33% (22%) reported from Lijiang (Cerro Pachón) observations (Gao et al, 2015;Liu et al, 2016). Gao et al (2015) and Liu et al (2016) also reported thermospheric layers in April, the latter with 46% occurrence. In addition to 15 April 2018 and 27 April 2018, we also observed a thermospheric layer on 27 April 2017 at Pingquan station (included as entry 12 in Table 1; there are no data at Yanqing).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although we are unable to compare with those in the polar region or tropic, as no statistics is available, it is much lower than the 33% (22%) reported from Lijiang (Cerro Pachón) observations (Gao et al, 2015;Liu et al, 2016). Gao et al (2015) and Liu et al (2016) also reported thermospheric layers in April, the latter with 46% occurrence. In addition to 15 April 2018 and 27 April 2018, we also observed a thermospheric layer on 27 April 2017 at Pingquan station (included as entry 12 in Table 1; there are no data at Yanqing).…”
Section: Discussionmentioning
confidence: 56%
“…Although we are unable to compare with those in the polar region or tropic, as no statistics is available, it is much lower than the 33% (22%) reported from Lijiang (Cerro Pachón) observations (Gao et al, 2015;Liu et al, 2016). Although we are unable to compare with those in the polar region or tropic, as no statistics is available, it is much lower than the 33% (22%) reported from Lijiang (Cerro Pachón) observations (Gao et al, 2015;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…At the same time, the wave also induces extremely low Na number density centered around 100 km: once during early evening and once more during late morning period. While the tidal wave contributions to Na s are quite limited due to their large temporal and spatial scales, large‐amplitude GW and the associated dynamic features can indeed generate small‐scale Na variations in the E region, such as Na s . In addition, the significant enhancement of eddy diffusion coefficient above the GW saturation level can change the Na s spatial and temporal structures dramatically. The tidal wind vertical wind component is found to be mainly responsible for the large‐scale Na layer extension into the thermosphere of midlatitude, which likely contributes to the Na layer observed in the thermosphere above low latitudes as well (Gao et al, ; Liu et al, ), where the tidal wave modulations are much stronger than those near midlatitude.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Plane et al () “pushed” an intense ion layer downward mathematically below 100 km in an Na chemistry model, and a sporadic Na layer was formed out of the E s . However, the formation of the Na layer/cloud above 100 km in the thermosphere reported around the globe (Clemesha, Batista, et al, ; Gao et al, ; Liu et al, ; Sarkhel et al, ) is puzzling, while the existing models currently do not generate these Na structures in the thermosphere. The Na ion‐molecular chemistry in the literatures limits the Na + neutralization above this altitude; thus, other mechanisms have to play significant roles in the Na variations in the E region, unless the current metal chemistry is missing some critical reactions.…”
Section: Introductionmentioning
confidence: 99%